O-OGC09 PD-1 inhibitors in Oesophageal Cancer: A systematic review of the oncological outcomes associated with PD-1 blockade and the evolving therapeutic landscape. (16th December 2021) - Whooley, Jack; Azzawi, Muhammed Al; Donlon, Noel; Bolger, Jarlath; Robb, William
Abstract: Background: Patients with oesophageal or gastro-oesophageal junction (GOJ) cancer that fail to respond to chemoradiotherapy have a poor clinical prognosis. Recent clinical trials have investigated the use of immune checkpoint inhibitors in these patients. The use of programmed cell death protein 1 (PD-1) inhibitors have emerged as exciting therapeutic options in other solid tumors, such as non-small cell lung cancer, renal cell carcinoma and melanoma. We assessed the efficacy and safety of PD-1 inhibitors in oesophageal and GOJ cancers. Methods: This systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive electronic literature search from the EMBASE, Pubmed, Scopus, MEDLINE and Google Scholar databases was conducted up to April 1 st 2021. Results: This review identified nine eligible studies reporting outcomes of 2149 patients treated with PD-1 blockade compared with 1244 patients treated with either a placebo or the standard regimen of chemotherapy for oesophageal and GOJ cancer. Clinically significant improvements in median overall survival have been demonstrated in advanced and metastatic oesophageal and GOJ cancer while maintaining acceptable safety profiles. Promising survival data has also recently emerged from PD-1 blockade in the adjuvant setting. Conclusions: PD-1 blockade in oesophageal and GOJ cancer has delivered impressive survival benefit whilst remaining well tolerated. Its use in the adjuvant setting may further advance our treatment options for this difficult-to-treat tumour, and more advancements in the immunotherapy landscape are highly anticipated. However, further characterization of the PD-1/PD-L1 pathway is required to optimise patient selection.